Predicting the 1RM from load-velocity relationship repetition - Jidovtseff, B.; Harris, N.; Cronin, J.; Crielaard, J. M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Determination of the 1RM is often considered to be problematic for populations such as the young as well as aged. As a result different methods have been developed to allow the estimation of 1RM from performing sub-maximal repetitions to failure (1). The accuracy of this method depends on several parameters such as the number of repetitions, type of exercise, training background and the population used (1). Very recently, authors have suggested to use the load-velocity relationship in order to determine the 1RM (2,3). The aim of the present study was to investigate the ability of such method to predict the 1RM in different strength exercises and with different technological devices. Methods: Data from five studies including in their protocol the 1RM determination and the load-velocity relationship profiling were gathered for the present analysis. Bench press, half-squat, horizontal press, leg curl and lat pulldown exercises were selected. A laboratory very accurate inertial dynamometer (4) was used for half-squat and bench press exercise. The Myotest (Myotsest, Switzerland) accelerometer was used for bench press, leg curl, horizontal press and lat pulldown exercises. Each study contain two sessions. The first was used for position standardisation, exercise familiarisation and 1RM determination. In the second session, velocity was measured at three or four increasing loads ranging from 30 to 95% of the 1RM. For each subject and each exercise, the best fit load velocity relationship and equation was determined. Associated parameters such as slope and intercept point on the Y axis were calculated and used for 1RM estimations. Results: Our study demonstrated contrasted results for the 1RM prediction using load-velocity relationship. Average velocity appears to be more relevant than peak velocity to estimate 1RM. The Myotest, that only allow peak velocity measurement, showed slightly lower prediction ability. With laboratory device, bench press 1RM prediction was practically perfect (r=0.98) providing evidence that the load-velocity relationship may be used to estimate 1RM with a standard error of estimate (SEE) of 7%. Acceptable correlations were observed with half-squat (r=0.76, SEE=11%), horizontal press (r=0.75, SEE=10%) and lat pulldown (r=0.62, SEE=8%) exercises. For equipment reason it was impossible to estimate the 1RM for the leg curl exercise. Discussion: Bench press results confirm the use of the load-velocity relationship in the 1 RM prediction. Unfortunately, prediction appears to be dependant from selected parameter, device, exercise and equipment.